Assessment of Social-Compatible Policies in Mineral Industry through the Internal Interested Parties - Petrova, Vesela (Research Papers, 2019)
The paper presents social and responsible practices and policies in two outstanding mining companies – “Asarel Medet” JSC and “Dundee Precious Metals Chelopech” JSC. It is focused on the internal stakeholders and their attitude to management, environmental protection, labor safety and staff training. The results of the empirical study show that the employees of the surveyed companies have an active attitude and understanding of the implemented company policies in the field of the indicated components of CSR, as well as revealing problems that the management of the respective company should solve in the future.
Keywords: Mining industry; Internal stakeholders